2016
DOI: 10.1016/j.scitotenv.2016.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter influences cerium translocation and physiological processes in kidney bean plants exposed to cerium oxide nanoparticles

Abstract: Soil organic matter plays a major role in determining the fate of the engineered nanomaterials (ENMs) in the soil matrix and effects on the residing plants. In this study, kidney bean plants were grown in soils varying in organic matter content and amended with 0-500mg/kg cerium oxide nanoparticles (nano-CeO2) under greenhouse condition. After 52days of exposure, cerium accumulation in tissues, plant growth and physiological parameters including photosynthetic pigments (chlorophylls and carotenoids), net photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 54 publications
1
24
1
Order By: Relevance
“…Similarly, our μXRF data is in contrast with the results from other studies on the same CeO 2 -NPs and treatment (500 mg kg −1 soil) used in this experiment which showed CeO 2 -NPs taken up in soy and kidney beans. 28,29 However, the absence of Ce particles/ aggregates inside the wheat roots, crowns and shoots at high CeO 2 -NPs concentration (500 mg kg −1 ) in the treatment and long exposure time (90 days of full life cycle) in our study strongly suggests that wheat does not take up or accumulate Ce from CeO 2 -NPs. Previous reports have also indicated root adsorption of CeO 2 -NPs and a lack of root-to-shoot translocation of Ce in wheat.…”
Section: Localization and In Situ Speciation Of Ce In Soil Columnscontrasting
confidence: 52%
See 1 more Smart Citation
“…Similarly, our μXRF data is in contrast with the results from other studies on the same CeO 2 -NPs and treatment (500 mg kg −1 soil) used in this experiment which showed CeO 2 -NPs taken up in soy and kidney beans. 28,29 However, the absence of Ce particles/ aggregates inside the wheat roots, crowns and shoots at high CeO 2 -NPs concentration (500 mg kg −1 ) in the treatment and long exposure time (90 days of full life cycle) in our study strongly suggests that wheat does not take up or accumulate Ce from CeO 2 -NPs. Previous reports have also indicated root adsorption of CeO 2 -NPs and a lack of root-to-shoot translocation of Ce in wheat.…”
Section: Localization and In Situ Speciation Of Ce In Soil Columnscontrasting
confidence: 52%
“…These results demonstrate that CeO 2 -NPs undergo very limited transformation in the wheat/soil system as consistently noted in previous synchrotron studies (Table S9 †). [29][30][31][32] However, this is the first study to exhibit synchrotron localization and speciation of CeO 2 -NPs in the rhizosphere (i.e. soil-root interface and areas in root vicinity).…”
Section: Localization and In Situ Speciation Of Ce In Soil Columnsmentioning
confidence: 90%
“…However, the authors demonstrated that CeO 2 ‐NPs were accumulated in plant tissues. In addition, the largest amount of CeO 2 ‐NPs was found in the roots of the radish, and a small amount of NPs was transported to the upper compartments, which corroborates the information obtained in several other studies . In fact, as the root is the edible part of the vegetable, and it is in direct contact with the soil, there is concern regarding possible contamination.…”
Section: Complementary Techniques For Characterization and Quantificasupporting
confidence: 89%
“…The Ce accumulation in fine roots and in the storage root showed that growth in loamy sand was higher than that in silty loam (Zhang, Musante, et al 2015). Kidney bean plants exposed to CeO 2 NPs for 52 days in a low organic matter soil usually possessed higher Ce concentration than the same tissues collected from an organic matter-enriched soil (Majumdar et al 2016). Likewise, different levels of phytotoxicity caused by CeO 2 NPs were found in lettuce seedlings incubated with three kinds of media, including agar (Cui et al 2014), potting mix soil and sand (Zhang et al 2017).…”
Section: Effects Of Different Growth Media On Np Phytotoxicitymentioning
confidence: 93%